Increasing Resilience and Competitiveness in the Sector of Small and Medium-Sized Enterprises (SME) in terms of Pandemic Restrictions and Military Threats - Szymon BERSKI; Dorota WOJTYTO; Joanna MICHALIK (Communications of International Proceedings, 2022)
The paper presents a proposal of a procedure for increasing resilience and competitiveness in the sector of small and medium-sized enterprises (SME) in terms of pandemic restrictions and military threats, based on the example of a metal processing company. In order to achieve the aim of the work, threats to SMEs in Poland in connection with the COVID-19 pandemic and the war in Ukraine were identified. It was proposed to increase the competitiveness of companies through the investment process in the modernization of the technological process with the use of financial support of companies by EU funds. A model of conduct for an exemplary company was also proposed, extended by the construction of a computer model supporting the process of technology development for SMEs from the metal products industry, for the construction of which computer modelling of the production process was used.
Keywords: COVID-19 and the war in Ukraine threats; EU funds; modelling of production cycle